Policing racist crime and violence : a comparative analysis - Oakley, Robin; European Monitoring Centre on Racism and Xenophobia (Vienna : EUMC, 2005)
Summary (s. 4-7).
Keywords: rasismi -- EU-maat; muukalaisviha -- EU-maat; rotusyrjintä -- EU-maat; väkivalta -- EU-maat; syrjintä -- EU-maat; asuminen -- EU-maat; työllisyys -- EU-maat; koulutus -- EU-maat; yhdenvertaisuus -- EU-maat